The Influence of Nursing Student Patient Safety Course (Nurse-PSC) in Increasing Patient Safety Competence in Nursing Students - Annisa Rahmi Galleryzki; Raymond Febrian Putra; Sekarini Sekarini; Lintang Puspita Prabarini; Ni Luh Ayu Sita Dewi; Haqi Masluqi; Fatimah Zahra (Adi Husada Nursing Journal, 2023)
Patient safety in hospitals cannot be separated from the role of nurses in providing nursing care. Nursing students who practice in the room are part of the system and are required to have patient safety competencies. Therefore, increasing safety competence is needed to support the quality of service by students during clinical practice. The purpose of the study was to determine the effect of the Nursing Student Patient Safety Course (Nurse-PSC) on safety competence (knowledge, skills and attitudes) before and after the course. The study was a quantitative study with a quasi-experimental design with a one-group pretest-posttest design approach. The number of respondents was 46 students who attended the course for eight weeks using e-learning collaboration and face-to-face meetings. Student competence was measured by Quality and Safety Competence (QSC) for bachelor nursing students (QSC-BNS) with 42 questions. The results showed that the respondents' patient safety competence increased significantly after the intervention (ρ < 0.001), all sub-variables of knowledge, skills, and attitude also showed significant improvement (p < 0.001). Therefore, the patient safety course model can be used as an effective form of learning to improve safety competence in nursing students.